1992
DOI: 10.1177/001872089203400407
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Test Phase of Usability Evaluation: How Many Subjects Is Enough?

Abstract: Attention has been given to making user interface design and testing less costly so that it might be more easily incorporated into the product development life cycle. Three experiments are reported in this paper that relate the proportion of usability problems identified in an evaluation to the number of subjects participating in that study. The basic findings are that (a) 80% of the usability problems are detected with four or five subjects, (b) additional subjects are less and less likely to reveal new infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
534
1
9

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 899 publications
(586 citation statements)
references
References 3 publications
18
534
1
9
Order By: Relevance
“…Flyvbjerg (2011) argues that rich data gathered from detailed, real life situations can provide meaningful insights, that could not be gained from context-independent findings. Virzi (1992), R.A (1992), when conducting research into usability, found 80% of problems, including the most severe, are detected with the first 4-5 subjects, illustrating how key insights can be gained with very small samples. Hancock et al (2009) also argue that ideographic case representations are increasingly relevant for the design of humanmachine systems, as advances in technology begin to focus on exploiting individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…Flyvbjerg (2011) argues that rich data gathered from detailed, real life situations can provide meaningful insights, that could not be gained from context-independent findings. Virzi (1992), R.A (1992), when conducting research into usability, found 80% of problems, including the most severe, are detected with the first 4-5 subjects, illustrating how key insights can be gained with very small samples. Hancock et al (2009) also argue that ideographic case representations are increasingly relevant for the design of humanmachine systems, as advances in technology begin to focus on exploiting individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-user assumption arose from two sources: (1) secondary analyses of other testers' data by Nielsen (1993) and (2) "law-of-diminishing-returns" arguments made by Virzi (1992). Both Nielsen (1993) and Virzi sought to demonstrate that statistical rigor can be relaxed considerably in real-world usability testing.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the foundational work of Nielsen (1993) and Virzi, it is appropriate to revisit the calculations and data on which the assumption was based. Virzi's (1992) It is widely assumed that 5 participants suffice for usability testing. In this study, 60 users were tested and random sets of 5 or more were sampled from the whole, to demonstrate the risks of using only 5 participants and the benefits of using more.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations